2006
DOI: 10.1016/j.jvs.2006.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Ambient pressure upregulates nitric oxide synthase in a phosphorylated-extracellular regulated kinase– and protein kinase C–dependent manner

Abstract: Intimal hyperplasia is the main cause for restenosis that complicates 10% to 30% of all such vascular procedures and 30% to 40% of endovascular procedures. This article provides some novel information about smooth muscle cell/endothelial cell interaction, one of the main regulators of vascular remodeling and intimal hyperplasia. The role of endothelial cell/smooth muscle cell interaction cannot be studied well in vivo because these interactions cannot be distinguished from other factors that coexist in vivo, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
(84 reference statements)
1
9
0
Order By: Relevance
“…New findings have shown the importance of crosstalk between PI3K/Akt and MAPK pathways. The regulatory interaction between components of Akt and MAPK cascades and NO synthesis by endothelial cells has been well documented [47]. Our results show that Akt, ERK and p38 may be involved in eNOS phosphorylation induced by olive oil polyphenols.…”
Section: Discussionsupporting
confidence: 61%
“…New findings have shown the importance of crosstalk between PI3K/Akt and MAPK pathways. The regulatory interaction between components of Akt and MAPK cascades and NO synthesis by endothelial cells has been well documented [47]. Our results show that Akt, ERK and p38 may be involved in eNOS phosphorylation induced by olive oil polyphenols.…”
Section: Discussionsupporting
confidence: 61%
“…Xu et al (28) also reported that the anti-infarct effect of NO donor S-nitroso-N-acetyl penicillamine was mediated by NOS-induced phosphorylation and activation of ERK1/2 in isolated rat cardiomyocytes and the intact heart, suggesting that ERK activation was downsteam of NOS (28). However, other studies demonstrated that ERK activation is required for the induction of NOS (3,24). Philipp et al (16) also reported that ERK phosphorylation occurred upstream of NOS in achetylcholine-induced protection in the rabbit heart.…”
Section: Discussionmentioning
confidence: 98%
“…Co-cultures of rat aortic endothelial and SMCs exposed to 130-135 mmHg of pressure show that ECs inhibit SMC proliferation and promote apoptosis likely through NO-dependent paracrine signaling (Vouyouka et al, 2006). ECs have been found to release significant amounts of the anticoagulant and vasodilator prostacyclin (Tokunaga et al, 1989) and increase production of the MMP collagenase (Kato et al, 1994).…”
Section: Pulsatile Pressurementioning
confidence: 99%